Measurement of safe and respectful maternity care in exit interviews following facility childbirth at the Lwala Community Health Centre (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Respectful maternity care is essential for ensuring positive childbirth experiences for women. It emphasizes moral values and respect for human rights and encourages behavior that considers women's preferences and needs for pregnant women, newborns, and their families. Maternity exit interviews conducted at Lwala Hospital assessed women's experiences during labor and delivery.Methods: A survey tool, Kobo Collect, was used for data collection among women who delivered at Lwala Hospital. 64 women of an age range of 17 and 36 years who delivered between October 1, 2023, and November 30, 2023, were interviewed. All the women had already given birth at least once. Results: Most of the women in the survey felt that they were given sufficient information to make informed decisions and felt comfortable during their delivery process. 86% strongly agreed that they were encouraged to have some light food, warm fluids, or tea during labor and birth. 72% of women said staff members talked to them about the advantages, disadvantages, and alternatives to treatments or procedures. Only 49% received information about caring for their babies. 13% felt they received information about where to get follow-up care. 96% felt the staff always protected their privacy at all stages. 80% said that the staff never scolded, shouted at, insulted, or made disrespectful comments. 91% said they were never touched by a staff member in a way that caused pain or felt inappropriate or non-consensual. 95% of women said all the staff care about what matters to the mother and her family. 85% of women were encouraged to feel confident in their ability to give birth. Despite 86% of the women feeling that the staff were active during labor, only 68% of women felt competence from the staff members during labor.Conclusion: Interviews underscore the importance of maternity exit interviews in assessing and enhancing the quality of maternity care. The outcomes of this research will inform future interventions and reinforce the commitment to providing respectful and equitable maternity care.